2016
DOI: 10.1038/ncomms13130
|View full text |Cite|
|
Sign up to set email alerts
|

Polarization of M2 macrophages requires Lamtor1 that integrates cytokine and amino-acid signals

Abstract: Macrophages play crucial roles in host defence and tissue homoeostasis, processes in which both environmental stimuli and intracellularly generated metabolites influence activation of macrophages. Activated macrophages are classified into M1 and M2 macrophages. It remains unclear how intracellular nutrition sufficiency, especially for amino acid, influences on macrophage activation. Here we show that a lysosomal adaptor protein Lamtor1, which forms an amino-acid sensing complex with lysosomal vacuolar-type H+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 44 publications
2
127
0
1
Order By: Relevance
“…Mechanistically, this involves the ability of mTORC1 to promote the effects of Akt on ATP-citrate lyase (Acly), thereby affecting gene-specific histone acetylation and the regulation of expression of a subset of genes that mark the alternatively activated state (Covarrubias et al, 2015). Consistent with this, in separate studies, Lamtor1 (a key component of the amino acid-sensing machinery), is found to play an essential role in the ability of macrophages to become alternatively activated in response to IL-4 (Kimura et al, 2016). …”
Section: Mtor In the Innate Immune Systemmentioning
confidence: 67%
“…Mechanistically, this involves the ability of mTORC1 to promote the effects of Akt on ATP-citrate lyase (Acly), thereby affecting gene-specific histone acetylation and the regulation of expression of a subset of genes that mark the alternatively activated state (Covarrubias et al, 2015). Consistent with this, in separate studies, Lamtor1 (a key component of the amino acid-sensing machinery), is found to play an essential role in the ability of macrophages to become alternatively activated in response to IL-4 (Kimura et al, 2016). …”
Section: Mtor In the Innate Immune Systemmentioning
confidence: 67%
“…BMDMs lacking FLCN are hypersensitive to LPS and CpG stimuli. LPS-mediated activation of canonical mTORC1 has been implicated in macrophage inflammatory response (25,26), and TFE3 and TFEB have recently been shown to drive mRNA expression of inflammatory genes in macrophages (23). We therefore reasoned that cells lacking FLCN, in which both of these pathways are activated, may be partially activated, even in absence of inflammatory stimulation, and/or may be hypersensitive to inflammatory signals.…”
Section: Tfe3 Promotes Canonical Mtorc1 Activity Through a Transcriptmentioning
confidence: 99%
“…Thus, the lysosomal adaptor protein Lamtor1, which forms an amino-acid sensing complex with V-ATPase, was recently shown to be required for M2 polarization [55]. Moreover, V-ATPase was reported to modulate macrophage polarization in tumor-bearing mice [56], and inhibition of the V-ATPase a2 isoform in murine tumor cells delayed tumor growth by decreasing M2-like TAMs in the tumor microenvironment [57].…”
mentioning
confidence: 99%